The transformation of rivers’ temperature regime downstream of reservoirs - Kirvel Ivan; Kukshinov Mikhail; Kirvel Pavel (Limnological Review, 2015)
The article is dedicated to the problem of the transformation of rivers’ temperature conditions influenced by artificial reservoirs. A quantitative estimation of average water temperatures over ten days, and maximum and average annual water temperatures of regulated rivers downstream of reservoirs was made on the basis of the data analysis of a complete period of instrumental observations of the Republican Hydrometeorological Centre of the Republic of Belarus. It is established that the character and the parameters of the transformation of temperature conditions of the regulated rivers along with morphometric features of the reservoirs are determined by the meteorological conditions of the year and the operating conditions of the water-engineering system. The length of the cooling period effect varies from 20 days downstream of small reservoirs to 50-70 days downstream of small and average size reservoirs. The warming effect is less significant by temperature, but lasts longer and is appreciable around 200-240 days in a year. An increase in the average annual water temperature up to 0.5°C and a decrease in maximum temperature down to 1.1°C are observed in the tail-water of average size storage pools. Small size storage pools demonstrate an annual increase in annual water temperature up to 0.3°C and a decrease in maximum temperature down to 0.3°C. Small size water pools show an increase both in annual water temperature up to 0.5°C and maximum water temperature up to 0.3°C. Typical changes in temperature conditions of rivers are observed for a distance of 130 kilometres below the dam of average size water pools, along 70 kilometres in small water pools and along 30 kilometres in tiny ones.